Pelatihan Kelompok Pendukung JAGO PALU Sebagai Upaya Meningkatkan Kualitas Hidup Lanjut Usia - Martini, Ni Made Dwi Ayu; Sari, Ni Luh Putu Dian Yunita; Darmaja, Ketut (Universitas Nusantara PGRI Kediri, 2022)
Quality of sexual life contributes to individual happiness and quality of life. However, the elderly are faced with stereotypes and myths that limit sexual life. Appropriate education about the elderly’s sexual life is expected to improve sexual quality which can then have a positive impact on the elderly’s quality of life. The role of elderly cadres, holders of elderly health programs at the Puskesmas, and caregivers is very large in increasing understanding of the importance of maintaining the elderly’s sexual activity and changing the mindset of the elderly and the community in responding to the elderly’s sexual life. JAGO PALU Support Group Training (Maintain Harmony through Increasing Elderly’s Sexual Activity) plays a role in increasing the right understanding of the elderly’s sexual activity. The service method uses virtual lectures, educational video screenings, and role-plays. Increased understanding of the sexual activity that is maintained in the elderly will improve the welfare of the elderly's sexual life which can improve the elderly’s quality of life.